2018
DOI: 10.1021/acsmacrolett.8b00667
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Reprocessable Cross-Linked Polyhydroxyurethanes Based on Disulfide Exchange

Abstract: Polymer networks that are cross-linked by dynamic covalent bonds often sacrifice the robust mechanical properties of traditional thermosets in exchange for rapid and efficient reprocessability. Polyurethanes are attractive materials for reprocessable cross-linked polymers because of their excellent mechanical properties, widespread use, and ease of synthesis, but their syntheses typically rely on harmful isocyanate precursors. Polyhydroxyurethanes (PHUs), derived from amines and cyclic carbonates, are promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(177 citation statements)
references
References 49 publications
3
174
0
Order By: Relevance
“…5b). 50 Their study also suggested that the incorporation of disulde containing diamine linkers not only changed the exchange rate but also the underlying temperature dependency (activation energy) from 131 AE 8 kJ mol À1 to 78 AE 4 kJ mol À1 .…”
Section: Vitrimer Hybrids: Combination Of Dynamic Bond Exchanges and mentioning
confidence: 96%
“…5b). 50 Their study also suggested that the incorporation of disulde containing diamine linkers not only changed the exchange rate but also the underlying temperature dependency (activation energy) from 131 AE 8 kJ mol À1 to 78 AE 4 kJ mol À1 .…”
Section: Vitrimer Hybrids: Combination Of Dynamic Bond Exchanges and mentioning
confidence: 96%
“…Similar outcomes in polyurethanes recycling were also achieved with disulfides as the dynamic links. Among many other examples disulfides were incorporated in polyhydroxyurethanes as detailed in recent work of Fortman et al114 Polyhydroxyurethanes, here derived from di‐ and triamines and cyclic carbonates incorporating disulfide bonds were shown to be recyclable by heat rapidly (in 30 s) at 150 °C. Transcarbamoylation reactions were considered as participating in the exchange, but the overall process was attributed primarily to disulfide exchange.…”
Section: Enabling Features and Emerging Applications Of Cansmentioning
confidence: 99%
“…Disulfide exchange has been well studied in dynamic materials . Generally, disulfide exchanges follow either anionic or radical pathways.…”
Section: Disulfide Exchange Chemistrymentioning
confidence: 99%